(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
The requirements of employers towards the employees have been gradually increasing. People tend to change their workplaces more frequently, therefore, it is necessary to regularly refreshment their knowledge and skills. The primart source of competitive and constantly adaptable knowledge is to train human resource in a targeted way. We consider such organizations successful where the training and improving of employees is handled as an investment. Training of human resource is a strategic question, due to that, none of the organizations should give up on its development tasks. An obliged factor of the training tasks is that due to the continuous changing in the circumstances, the knowledge itself are amortized; therefore, it needs to be permanently improved as well. The employee will be capable of cope with the requirements if the gap between the scope of work activities and his personal competences is narrow. Thus the competence based training system is a constant development within the organization.